Hands across frontiers: case studies in technical cooperation - Teaf, Howard Morris; Franck, Peter G. (Ithaca, N.Y., Distributed by Cornell University Press, 1955)
Hands across frontiers: case studies in technical cooperation examines technical assistance across the world in the 1950's. Areas covered include: Technical assistance through the UN in 1950-53; Land reforms in Taiwan; agricultural extension in Peru; Hookworm campaign in Ceylon (Sri Lanka); industrial development and others.
Includes bibliographical references.
lje 11/05/2018
Loans
Keywords: Technical assistance